2011
DOI: 10.1590/s0074-02762011000100003
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behavior of Triatoma vitticeps (Reduviidae: Triatominae) in the state of Minas Gerais, Brazil

Abstract: The objective of this study was to evaluate the feeding behavior of Triatoma vitticeps through the identification of its food sources and the characterization of the blood ingestion process. In addition, we aimed to verify if the saliva of this vector interferes with the perception of the host during the feedings by creating a nervous impulse. Here, we demonstrated that the T. vitticeps saliva reduces, gradually and irreversibly, the amplitude of the compound action potential of the nervous fibre, which helps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…It is known that blood meals from Triatoma spp. may contain DNA from more than one vertebrate species [4], [14], [25], [26]. Thus, an important consideration for blood meal analysis is the ability to detect blood from more than one host in a single triatomine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that blood meals from Triatoma spp. may contain DNA from more than one vertebrate species [4], [14], [25], [26]. Thus, an important consideration for blood meal analysis is the ability to detect blood from more than one host in a single triatomine.…”
Section: Discussionmentioning
confidence: 99%
“…Digestion with Hae III alone resulted in a mouse identification compared to the double digest that resulted in blood meal identification as human. This technique allowed for the rapid and inexpensive identification of both hosts in comparison to the common practice of running several species-specific PCR reactions or the use of DNA sequencing of PCR amplified products [3],[4],[26].…”
Section: Discussionmentioning
confidence: 99%
“…This is due primarily to the transmission of Trypanosoma cruzi by Triatoma infestans, which also lives in human dwellings 29 . Thus, dogs and cats play an important role in the maintenance of the disease, in addition to other domestic and wild mammals that frequent the areas surrounding homes 3,4,12 . In the case of cats, although infection rates are low, their association with the domestic cycle is closely associated with their wandering habits 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Vector transmission has always been considered to be the most important mode of transmission in Brazil, corresponding to 80% of cases of parasitic diseases, and is associated with the ability of these triatomines to invade and adapt to homes and outbuildings, especially those of low socioeconomic conditions 3,4 . Carlos Chagas correlated this trypanosomiasis transmission with the presence of triatomines in intra-domestic areas 5 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies also showed eclectic feeding by T. vitticeps. The longer contact period with the host required to obtain a complete meal compared with other triatomine species of the same instar could favor the presence of multiple blood sources in T. vitticeps under natural conditions as has been suggested by the precipitin test 29 . Marsupials, rodents and birds are the most frequent food sources for this species.…”
Section: Epidemiological Evaluationmentioning
confidence: 92%